PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR DWIBAHASA SEBAGAI SARANA APRESIASI SASTRA KELAS IV SEKOLAH DASAR - Khusnul Khotimah; Rina Yuliana; Sundawati Tisnasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to find out the development of bilingual picture book media as a tool of literary appreciation at grade IV of elementary school, to determine the feasibility of the bilingual picture book, and to find out students’ response to the bilingual picture book media. This research was conducted at SDN Kotasari involving 22 students in class IV-A. 10 students were tested in a limited trial. The type of research referred to the Borg and Gall model modified by Sugiyono. This model consisted of six stages namely problem analysis, data collection, product design, design validation, design revision and product trial. The instruments used were questionnaires for media validation by lecturers and student questionnaire sheets. Based on the data analysis, several findings were obtained, among others, the quality of the bilingual picture book was categorized as very feasible with a percentage of 86% according to two media experts, very feasible with a percentage of 82.5% according to two linguists, and 91.5% according to two material experts. Then, the percentage from the students’ responses was 89% with very good category. Thus, it was concluded that bilingual picture book media could be used in learning literary appreciation at grade IV of elementary school.